Comparison of Ultrasonographic Assessment of Cross Sectional Area of the Median Nerve in the Diagnosis of Carpel Tunnel Syndrome with Nerve Conduction Studies - Saima Shan, Asim Rehman, Sadaf Nasir, Taqdees Khaliq, Riaz Mahmood, Ghulam Mujtaba (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Carpal Tunnel Syndrome (CTS) is a common problem which interferes with the normal use of the hand. It has general population prevalence of 16%. Objective: The objective of this study was to determine the validity of high-resolution ultrasound (US) in carpal tunnel syndrome in adult patients using nerve conduction studies (NCS) as gold standard. Study design & Settings: Cross sectional validation study with purposive (non-probability) sampling conducted in the Department of Diagnostic Radiology, Federal Government Polyclinic Hospital, Islamabad in collaboration with outdoor departments of Neurology and Rheumatology of the same hospital. Study duration: The study was conducted in Federal Government Polyclinic Hospital Islamabad for duration of one year, from November 2021 to November2022. Methods : 152 patients were included in study group who underwent ultrasound by using 12 – 15MHz linear transducer. Later on their nerve conduction studies were performed & results were compared. Results: There were 152 patients included in the study, with 47 (30.9%) males and 105 (69.1%) females and overall mean age of 33.74±11.58 years. The sensitivity of ultrasound to detect carpel tunnel syndrome was calculated to be 90.6% while specificity was found to be 82.52 %. The positive predictive value, negative predictive value and diagnostic accuracy of 86.5%, 87.3% and 86.8% was reported, respectively. Conclusion: High resolution US is an accurate imaging study with diagnostic accuracy of 86.8% and gives results comparable to NCS. It can be used in patients unsuitable for the latter modality. Keywords: Carpel tunnel syndrome (CTS), ultrasound (US), Nerve conduction studies (NCS).